Communication restriction in adults who stutter: Part II. (2nd July 2016) - Lee, Amanda; Robb, Michael; van Dulm, Ondene; Ormond, Tika
ABSTRACT: This article presents a follow-up study to Lee, van Dulm, Robb, and Ormond (2015). The aim was to explore communication restriction in adults with stuttering (AWS) using typical language measures and systemic functional linguistics (SFL) analyses. The article compared the pre- and post-treatment performance of AWS in language productivity and complexity, transitivity, modality, appraisal, and theme. Ten-minute conversational samples were obtained from 20 AWS before and after participation in intensive stuttering treatment. Transcripts were analysed for quantity and complexity of verbal output, and frequency of transitivity, modality, appraisal and theme resources. Between pre- and post-treatment, the following differences were observed: (1) a significant increase in frequency of modal operators, and trends approaching significance for (2) increased language complexity (3) increased language expressing appraisal. These changes suggest increased flexibility of language use in AWS following treatment, particularly towards interpersonal engagement. The value of SFL to this area of research is discussed.